2017
DOI: 10.1007/s13197-017-2946-4
|View full text |Cite
|
Sign up to set email alerts
|

The bioaccessibility of iodine in the biofortified vegetables throughout cooking and simulated digestion

Abstract: Biofortification of crops with exogenous iodine is a novel strategy to control iodine deficiency disorders (IDD). The bioaccessibility of iodine (BI) in the biofortified vegetables in the course of soaking, cooking and digestion, were examined. Under hydroponics, the concentration of iodine in leafstalks of the celery and pakchoi increased with increasing exogenous iodine concentration, 54.8-63.9% of the iodine absorbed by pakchoi was stored in the soluble cellular substance. Being soaked in water within 8 h, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
2
18
0
3
Order By: Relevance
“…The increase was 2.5 times higher with I – -supply than with IO 3 – -supply. Similar effects on the influence of the level and form of I supply were described in studies on the biofortification of strawberries ( Li et al, 2017 ) and various vegetable and cereal crops ( Hong et al, 2008 ; Voogt et al, 2010 ; Cakmak et al, 2017 ; Li et al, 2018 ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The increase was 2.5 times higher with I – -supply than with IO 3 – -supply. Similar effects on the influence of the level and form of I supply were described in studies on the biofortification of strawberries ( Li et al, 2017 ) and various vegetable and cereal crops ( Hong et al, 2008 ; Voogt et al, 2010 ; Cakmak et al, 2017 ; Li et al, 2018 ).…”
Section: Discussionsupporting
confidence: 58%
“…So far, little is known about which of these organic I species play a major role in I-fertilized plants. Nevertheless, several studies conducted in vitro and as clinical trials indicate that biofortified I remains largely bioavailable in plant foods ( Tonacchera et al, 2013 ; Li et al, 2018 ; Cakmak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Iodine biofortification of leafy vegetables was obtained in spinach [ 8 , 9 ], lettuce [ 10 , 11 , 12 ], and celery [ 8 , 13 ]. Among Brassicaceae , some studies of cabbage and Chinese cabbage [ 7 ], pak choi [ 14 ], and radish [ 15 ] have been carried out. In an I biofortification program, food safety is a non-negotiable point in order to avoid the risk of exceeding the I tolerable upper intake level (500–600 µg/day) in the diet [ 4 ] and, at the same time, to avoid limits to the consumption of biofortified vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products from plant have served as important sources of lead compounds for developing drugs. Notably, many studies found that Traditional Chinese Medicine (TCM) extract effectively inhibited the activity of ACE [11,12]. Moreover, medicinal and edible plants are safe and effective play an important role in supporting healthcare both in China and around the world.…”
Section: Introductionmentioning
confidence: 99%